Code Mixing of Raymond Chin in His YouTube Channel - Faradiba Sari Harahap (Journal of English Language Teaching, Literatures, Applied Linguistic (JELTLAL), 2025)
Code mixing of English is a very common phenomenon observed in spoken language in our country. The objective of the research is to analyze the type of code mixing uttered by Raymond Chin, a millennial entrepreneur and content creator from Indonesia who often uploads content in Indonesian mixed with English in his YouTube channel. There are five types of insertion of code-mixing, such as in elements of words, phrases, clauses, hybrid, and repetition. From 83 data of code mixing found in one of his YouTube contents, entitled “Bangun Siang = Orang Miskin? Orang Sukses Bangun Jam 5 Pagi”, insertion of the word shows 53 data or 63.85 % which consist word class of noun, verb and adjective.  In phrase shows  23 data ( 27.71 %) which consist of noun, adjective, verb, and prepositional phrases. In insertion of the clause shows 4 data (4.81 %) and in repetition shows 3 data (3.61 %) which consist independent clauses.  The most dominant type of insertion of code mixing in this research is insertion of word. Code mixing here occurs when the speaker (Raymond Chin) inserts an element of a foreign language (English) in an utterance when he mostly communicates in Indonesian as his first language.